A trapping-evacuation technique for giant carotid-ophthalmic segment aneurysm clipping in a hybrid operating theater. Issue 7 (July 2015) - Hu, Peng; Zhang, Hong-Qi; Li, Gui-Lin; He, Chuan; Bian, Li-Song; Zhi, Xing-Long; Ling, Feng
Abstract It is essential to collapse giant carotid-ophthalmic (OA) segment aneurysms for successful microsurgical clipping. We present a trapping-evacuation technique utilising hybrid operating theater capabilities to soften OA aneurysms. The patients were prepared for both microsurgical and endovascular procedures. After the majority of the aneurysm was exposed, a balloon was placed at the orifice of the aneurysm to fully block the blood flow. When the balloon was inflated, blood was evacuated from the aneurysm sac to eliminate the space occupying effect. Subsequently, the aneurysm neck was clearly exposed which greatly facilitated clip placement. A control angiogram was obtained prior to closing the wound to ensure complete aneurysm obliteration. After the establishment of a hybrid operating theater in our hospital, two aneurysms were successfully clipped using this technique. Although postoperative complications occurred in both patients, none of the events were related to the endovascular procedure or the trapping-evacuation technique. As a well-organized procedure designed for use in a hybrid operating theater, the current trapping-evacuation technique is an option for the surgical clipping of giant OA aneurysms.